Peranan Audit Internal Pada Pembiayaan Kelompok Mikro Perempuan Dalam Upaya Pencegahan Frauding - Dwi Ermayanti Susilo (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2021)
The purpose of this study was to see how the role of internal audit on women's microfinance at PNM Mekaar in fraud detection and prevention. The research used a qualitative approach, making direct observations, conducting interviews and collecting data in the form of documents carried out by internal audits. Where the company's internal audit is active on the financing of women's micro groups in the prevention of fraud with evidence in the 2017 examination which revealed that during the examination of 4 groups there was no fraud, including delinquency in payment of insurance claims, customers who died had not received complete insurance documents, the use of bailout funds by one of the customers, monitoring activities are not in accordance with the control provisions which must be done once a month and billing statements for three customers who have paid three times but are not recorded by the head office system.